Improved single particle ICP-MS characterization of silver nanoparticles at environmentally relevant concentrations. Issue 10 (15th September 2016) - Newman, Karla; Metcalfe, Chris; Martin, Jonathan; Hintelmann, Holger; Shaw, Phil; Donard, Ariane
Abstract : Improved single particle ICP-MS characterisation of Ag nanoparticles in a lake ecosystem using microsecond dwell times. Abstract : Single particle ICP-MS (spICP-MS) is a useful tool for characterizing and quantifying suspensions of metallic nanoparticles, but there are currently limitations on the minimum size of nanoparticles that can be detected using this technique. In this study, we demonstrated the spICP-MS capabilities of a double focusing magnetic sector ICP-MS instrument for analysis of commercially available Ag NP suspensions and samples of Ag NPs suspended in natural lake water, including data on particle event integration and sizing, particle counting and measurement of dissolved Ag background. Analysis of commercially available AgNP suspensions using a dwell time of 30 us determined that the ionic background dependent size detection limit is ∼10 nm at 2.7 ng Ag L −1 . In samples collected from a lake in which AgNPs were added experimentally (PVP-capped, 30–50 nm size distribution), the Ag NPs were shown to have a modal diameter of ∼20 nm, with a dissolved Ag background of 6–13 ng L −1 . The minimum particle size detectable in the lake water samples was approximately 15–18 nm, depending on the dissolved Ag concentration. There was no evidence of matrix effects in lake water that would adversely affect the accuracy of the particle sizing. The determination of particle number concentrations by spICP-MS was shown to be limited by particle size dependent transport efficiencies and losses through adsorption on sample vials. Overall, while further development of the sample preparation protocols is needed, the spICP-MS technique described in this study demonstrates improved discrimination of AgNPs from dissolved Ag and a lower particle size range relative to previously described instrumental methods.